Peran Balai Latihan Kerja Samarinda Mengurangi Tingkat Pengangguran Pada Masa Pandemi Covid-19 dalam Perspektif Ekonomi Islam - Ratna kartiasari; Bambang Iswanto; Irma Yuliani; Tika Parlina (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2022)
Abstract Currently, the unemployment rate has increased due to an outbreak of the Covid-19 virus that has attacked the whole world, including Indonesia. The number of unemployment that occurs in each region, it is the responsibility of the government and society to immediately tackle the number of unemployment that occurs. This research is a qualitative type of research using a descriptive qualitative approach. The source of the data used is primary data obtained from interviews with BLK Samarinda. The technique used in data collection is by using observation, interview, and documentation techniques. The results obtained from this study indicate that the training programs carried out during the pandemic there were 13 vocational training programs running well and effectively. The role of the Samarinda Cooperation Training Center in assisting the government in unemployment is by providing facilities to training participants in the form of facilities, infrastructure and training programs during free training. The obstacle faced during the training was the delay in the implementation of OJT due to the Covid-19 pandemic so that the solution was not required to implement OJT. The view of Islamic Economics on the role of the Samarinda Cooperation Training Center in reducing unemployment is in accordance with the principles of Islamic Economics, namely Kafa'ah, Himmatul-amal and Amanah. Keywords: Islamic Economics, The Role of the Job Training Center, Unemployment.